Hilirization Obligations for Mining Companies with Contract of Works Status In Indonesian Positive Law - Sudaryat, Sudaryat (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2024)
The Indonesian government requires mineral and coal mining companies to reduce exports of raw minerals, in fact some raw minerals (ore) are prohibited from being exported abroad, such as nickel and several more minerals will follow. Mining companies are required to process and purify raw minerals domestically (downstreaming) so that these minerals have better added value than before. The fact is that some mining companies operating in Indonesia have work contract status, some have IUP status and some have IUPK status. Currently there are several companies with work contract status that have become IUPK. The Mineral and Coal Law has also undergone several replacements and changes and the results of a study show that the Indonesian Government is inconsistent in its policy on downstreaming metallic minerals. The work contract was signed before Law No. 4 of 2009 came into effect. There is doubt about the implementation of downstreaming for metal mineral mining companies with work contract status. The aim of the research is to examine the downstream obligations for metal mineral mining companies with work contract status in the substance of the work contract both before being amended and those which have been amended and to find out the downstream obligations in the Mineral and Coal Law which has undergone several changes for metal mineral mining companies with status. work contracts that have not yet been converted into IUPK. The research method used is normative juridical with a descriptive analysis research approach. This research is a literature study of primary legal materials, secondary legal materials and tertiary legal materials. The data collected was analyzed using qualitative juridical methods. The research results show that in the substance of the work contract before the amendment and after it was amended after the enactment of Law No. 4 of 2009 concerning Minerals and Coal, it turns out that there is an obligation in the work contract for the company holding the work contract to carry out downstreaming, including the downstreaming mechanism.   Then, if we analyze the mineral and coal law, namely from Articles 102, 103 and 104 of Law No. 3 of 2020, there is no express downstream obligation for metal mineral mining companies with work contract status, but there is an express downstream obligation for metal mineral mining companies with contract status but it was listed in Article 170 of Law No. 4 of 2009 and implied in Article 170A of Law No. 3 of 2020. The time limit for downstream implementation for companies holding work contracts starts from the time the company holding the work contract starts production. The downstream obligation itself will be optimal if it is in line with the policy of banning raw mineral exports.